A study of menstrual disturbance in cases of fibroid uterus - Khyade, Rajeshwari Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Leiomyoma’s also called fibroids due to their abundant fibrotic tissue have a 70-80% cumulative incidence in childbearing years. Fibroids are the most common occurring benign tumors. Fibroids represent a tremendous public health burden on women and economic cost on society. Methods: It is prospective study done over a period of one year, 50 cases presenting to the obstetrics and gynecology department. Women included were in their reproductive age between 30-55 yrs. of age and had experienced menstrual bleeding complaints. Results: The prevalence of uterine fibroids ranged from 46% in age group 41-45yrs, 24% in 46-50yrs, and 11% in 36-40yrs. Women with uterine fibroids complained of menorrhagia in 78%, dysmenorrhea in 30%, metrorrhagia in 10%, polymenorrhea 22%, pain in abdomen 22%, urinary problem 8%, SCOPV 6%, primary infertile 4%, leucorrhea 12% and lump in abdomen 4%. Conclusions: Uterine fibroid is a common problem in women of reproductive age causing various bleeding and pain symptoms that can have negative impact on various aspects of women’s life.